TO THE PROBLEM OF PROFESSIONAL TRAINING OF PSYCHOLOGISTS: CRITERIA AND LEVELS OF READINESS OF PRACTICAL PSYCHOLOGISTS FOR HEALTH PRESERVATION BY MEANS OF RECREATIONAL RESOURCES - Danylchuk, Larysa; Yurkiv, Yaroslava (Personality and environmental issues, 2025)
The article reveals the scientific and theoretical foundations for determining the criteria and levels of readiness of practical psychologists for health preservation by means of recreational resources as an important condition for maintaining psychophysiological, mental, and social health under martial law in Ukraine.It is emphasized that the effectiveness of recreational activity largely depends on the formation of the integrative readiness of practical psychologists, which includes axiological orientation, motivational focus, knowledge, critical thinking, emotional stability, volitional self-regulation, and practical activity.The purpose and scientific novelty are defined by the fact that the author proposes a criterion-indicative system encompassing four key criteria: axiological-motivational, cognitive-critical, emotional-volitional, and recreational-activity. The indicators of each criterion are described in detail, allowing for both qualitative and quantitative assessment of the degree of readiness.Based on this, three levels of readiness are identified – high, medium, and low – each characterized by specific attitudes toward health, motivation, knowledge, emotional-volitional qualities, and the level of involvement in recreational activities.It is emphasized that identifying the criteria and levels of readiness provides a foundation for further empirical research and the implementation of psychological support and preventive measures in the professional environment. Prospects for further research are associated with the development of effective psychological support programs and the formation of a health-preserving culture among practical psychologists.